Kegiatan Bercerita untuk Melatih Kemampuan Berbicara Anak di PAUD Mandiri Gemilang Cirebon - Indah Purwanti; Supriyatun Supriyatun; Eti Juhaeti (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2023)
This research was motivated by the results of the development of expressive language which had not yet developed optimally, so efforts were made to improve it with the aim of stimulating children's speaking abilities through storytelling activities. This type of research uses Classroom Action Research (PTK), with a Hopkins design carried out in two cycles. The results of the research showed that there was an increase in children's interest and enthusiasm in participating in activities, as well as an increase in children's speaking abilities from the first cycle to the second cycle by 22%. It can be concluded that storytelling activities can improve children's ability to greet friends, introduce themselves, talk about their hobbies and experiences in front of the class.